The Role of Shallot Farming in Household Income in Sampungu Village, Soromandi District, Bima Regency - Safirah Safirah; Wahidin Wahidin; Muhammad Alwi (LPPM Sunan Doe, 2023)
This research aims to find out how much net income is from shallot farming and what is the average income from shallot farming. This study uses a quantitative approach with descriptive analysis. The research location was carried out in Sampungu Village, Soromandi District, Bima Regency, data collection techniques in this research used questionnaires, interviews and documentation. The sampling technique in this study was simple random sampling with a total sample of 17 people. The research results obtained in this research are that the net income of shallot farming is (IDR) 709,835,508.00 and the average income of shallot farming is (IDR) 41,755,029.00. Then the total costs incurred during onion production red is (IDR) 434,164,492.00.